Revisiting the Past to Understand the Present: The Linguistic Ecology of the Singapore Deaf Community and the Historical Evolution of Singapore Sign Language (SgSL) - Tay, Phoebe; Ng, Bee Chin (Frontiers in Communication, 2022)
Singapore, a young nation with a colonial past from 1819, has seen drastic changes in the sociolinguistic landscape, which has left indelible marks on the Singapore society and the Singapore deaf community. The country has experienced many political and social transitions from British colonialism to attaining independence in 1965 and thereafter. Since independence, English-based bilingualism has been vigorously promoted as part of nation-building. While the roles of the multiple languages in use in Singapore feature prominently in the discourse on language planning, historical records show no mention of how these impacts on the deaf community. The first documented deaf person in archival documents is a Chinese deaf immigrant from Shanghai who established the first deaf school in Singapore in 1954 teaching Shanghainese Sign Language (SSL) and Mandarin. Since then, the Singapore deaf community has seen many shifts and transitions in education programming for deaf children, which has also been largely influenced by exogeneous factors such as trends in deaf education in the USA. A pivotal change that has fair-reaching impact on the deaf community today, is the introduction of Signing Exact English (SEE) in 1976. This was in keeping with the statal English-based bilingual narrative. The subsequent decision to replace SSL with SEE-II has dramatic consequences for the current members of the deaf community resulting in internal divisions and fractiousness with lasting implications for the cohesion of the community. This publication traces the origins of Singapore Sign Language (SgSL) by giving readers (and future scholars) a road map on key issues and moments in this history. Bi- and multi-lingualism in Singapore as well as external forces will also be discussed from a social and historical perspective, along with the interplay of different forms of language ideologies. All the different sign languages and sign systems as well as the written/spoken languages used in Singapore, interact and compete with as well as influence each other. There will be an exploration of how both internal factors (local language ecology) and external factors (international trends and developments in deaf education), impact on how members of the deaf community negotiate their deaf identities.